2021
DOI: 10.3390/ijerph18157922
|View full text |Cite
|
Sign up to set email alerts
|

Association between First Sexual Intercourse and Sexual Violence Victimization, Symptoms of Depression, and Suicidal Behaviors among Adolescents in the United States: Findings from 2017 and 2019 National Youth Risk Behavior Survey

Abstract: The objective of this study was to investigate the association between first sexual intercourse and sexual violence victimization, symptoms of depression, and suicidal ideation among sexually active adolescents in the United States. Data for this study came from the U.S. 2017 and 2019 iterations of the National Youth Risk Behavior Survey. An analytic sample of 6252 adolescents aged 14–18 years old (49.5% female) who reported ever having sexual intercourse was analyzed using Poisson regression. The outcome vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 58 publications
0
8
0
1
Order By: Relevance
“…The available evidence on the effect of sexual violence in mid-adolescence on mental health is scarce, because many studies evaluating the effects of sexual violence before adulthood have focused on adverse childhood experiences (including sexual abuse earlier in childhood 8 , 9 ), experiences of sexual violence in the university and college environment, 10 , 11 and intimate partner violence in older adolescent age groups. 12 Several studies we identified that focused on mid-adolescence—during which many individuals begin to experience increasing rates of sexual harassment and assault after puberty—cannot make assumptions on the population-level effects of sexual violence due to the use of selective samples (eg, samples recruited from sexual-assault referral centres 13 ), the examination of cross-sectional associations, 14 , 15 or the use of retrospective recollections of both the violence experienced and its perceived subsequent effect on mental health. 7 , 16 Previous studies with longitudinal examination have been limited by the use of convenience samples in some North American school settings.…”
Section: Introductionmentioning
confidence: 99%
“…The available evidence on the effect of sexual violence in mid-adolescence on mental health is scarce, because many studies evaluating the effects of sexual violence before adulthood have focused on adverse childhood experiences (including sexual abuse earlier in childhood 8 , 9 ), experiences of sexual violence in the university and college environment, 10 , 11 and intimate partner violence in older adolescent age groups. 12 Several studies we identified that focused on mid-adolescence—during which many individuals begin to experience increasing rates of sexual harassment and assault after puberty—cannot make assumptions on the population-level effects of sexual violence due to the use of selective samples (eg, samples recruited from sexual-assault referral centres 13 ), the examination of cross-sectional associations, 14 , 15 or the use of retrospective recollections of both the violence experienced and its perceived subsequent effect on mental health. 7 , 16 Previous studies with longitudinal examination have been limited by the use of convenience samples in some North American school settings.…”
Section: Introductionmentioning
confidence: 99%
“…Depression and suicidal ideation are worldwide concerns and they are the most common mental health problems (Bilsen, 2018;Perquier et al, 2021;Pozuelo et al, 2022). Existing studies indicated that 19.6-30.6% of adolescents suffered from depression (Song et al, 2008;Ibrahim et al, 2013;Gao et al, 2020), while 18-26.4% (Baiden et al, 2021;Hu et al, 2021;Mahumud et al, 2021) had suicidal ideation. In recent years, another mental problem, i.e., uncertainty stress, has attracted some attention from scholars (Holland and Wheeler, 2016), because it can arouse worse consequences and influences than life stress and study stress (Wu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of adolescents in 38 countries (6), it was reported that suicide attempts and sexual relationships were related, and the same results were reported in a study of Baiden et al (36). The current study showed that sexual intercourse among adolescents was associated with problematic behaviors-such as drinking, smoking, and drug use-and psychological behaviors-such as loneliness, sadness, despair, suicidal ideation, and suicidal attempts-that could occur together (2,36). Furthermore, a Swedish study found that girls who experienced sexual intercourse at an early age had poor physical and mental health (2).…”
Section: Discussionmentioning
confidence: 95%